Sexual exploitation of teenagers : adolescent development, discrimination, and consent law - Drobac, Jennifer Ann (Chicago ; London : The University of Chicago Press, 2016)
"When it comes to sexual relationships, adolescents pose a particular problem. Few teenagers possess all of the emotional and intellectual tools needed to navigate these threats, including the all too real advances made by supervisors, teachers, and mentors. The author explores the shockingly common problem of maturing adolescents who are harassed and exploited by adults in their lives. Reviewing the neuroscience and psychosocial evidence of adolescent development, she explains why teens are so vulnerable to adult harassers. Even today, in an age of increasing public awareness, criminal and civil law regarding the sexual abuse of minors remains tragically inept and irregular from state to state. Drobac uses six recent cases of teens suffering sexual harassment to illuminate the flaws and contradictions of this system, skillfully showing how our current laws fail to protect youths, and offering an array of imaginative legal reforms that could achieve increased justice for adolescent victims of sexual coercion"--Book jacket.
Introductions : Sara's case, sexual exploitation, and legal terms -- Adolescent worldliness : sexual harassment targeting teenagers -- Adolescent development : wisdom regarding teen capacity -- Legal treatment of worldly adolescents and criminal law treatment of unwise adults -- The development of civil law's response to worldly women and precocious teenagers : historical wisdom or oppressive judgment? -- Modern worldly wisdom? : the theoretical foundations of antidiscrimination and sexual exploitation law -- Wising up in the workplace : modern antidiscrimination law and its application -- The evolution of conflicting law in California and perhaps beyond -- Students who "lov'd not wisely but too well" and the biases that influence adults in judgment -- Becoming wiser : public policy, developing capacity, the law, and legal assent -- Acknowledgments -- Appendix 1 : Common forms of sexual harassment -- Appendix 2 : Summary of state juvenile sex crime statutes.
Includes bibliographical references (pages 263-332) and index.
Keywords: Sexual harassment of women -- Law and legislation -- United States; Teenagers -- Legal status, laws, etc. -- United States; Sexual consent -- United States; Sexual harassment -- United States -- Prevention; Teenagers -- Sexual behavior -- United States